2021
DOI: 10.1111/ctr.14377
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of Bacillus Calmette‐Guerin intravesical therapy in kidney transplant recipients with superficial bladder cancer

Abstract: Kidney transplantation increases the life expectancy of recipients; however, it also increases three-fold the risk of urothelial cancer. 1 In fact, de novo bladder cancer (BC) can be diagnosed many years after kidney transplantation, with smoking being the most important risk factor. [1][2][3][4][5] Most BCs in kidney transplant recipients are non-muscle-invasive (NMIBC) and are characterized with an aggressive course. 1 Bacillus Calmette-Guerin (BCG) is an attenuated form of Mycobacterium bovis that can be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, its use in the renal transplant population remains controversial due to concerns about the safety of using BCG in an immunosuppressed state [ 17 ]. Although some studies have shown that bladder infusion chemotherapy with BCG is both safe and effective [ 18 , 19 ], there have been cases of systemic infection following bladder infusion with BCG [ 20 ]. In this study, we used non-live vaccine-like drugs, such as epirubicin and mitomycin, for bladder instillation.…”
Section: Discussionmentioning
confidence: 99%
“…However, its use in the renal transplant population remains controversial due to concerns about the safety of using BCG in an immunosuppressed state [ 17 ]. Although some studies have shown that bladder infusion chemotherapy with BCG is both safe and effective [ 18 , 19 ], there have been cases of systemic infection following bladder infusion with BCG [ 20 ]. In this study, we used non-live vaccine-like drugs, such as epirubicin and mitomycin, for bladder instillation.…”
Section: Discussionmentioning
confidence: 99%